Microbial Growth as Determinant of Antibiotic Production with Biotic Elicitors Stimulation - Citra Hardiyanti; Khairullinas Khairullinas; Jeky Sasemar Lumban; Titania Tjandrawati Nugroho; Yuana Nurulita (Jurnal Kimia Sains dan Aplikasi, 2020)
An antibiotic-resistant and multidrug-resistant (MDR) issue open the role of researchers to continue to search for natural potential as a source of new antimicrobials. One of the potential fungi isolates that can produce antimicrobial active compounds from Indonesian tropical peat soils is Penicillium sp. LBKURCC34. In this study, the production of antimicrobial compounds from local isolates was carried out by batch fermentation method in liquid media with the addition of biotic elicitors to increase the extraction activity and yield. This study aims to optimize the results based on the time the elicitor is added. Staphylococcus aureus was used as a biotic elicitor, which was added on days 2, 3, and 4 in the production of antibiotics by fermentation incubation of 6-14 days. The antibiotic production media was extracted with ethyl acetate and evaporated. The antimicrobial test was carried out by the disk diffusion method against pathogenic bacteria Escherichia coli, Staphylococcus aureus, Bacillus subtilis, and Staphylococcus epidermidis using three crude extract contents (19; 38; and 57 µg/disc). Amoxicillin® was used as a positive control (10 µL/disc). The results showed that the addition of S. aureus biotic elicitor extended the log phase growth of the fungus Penicillium sp. LBKURCC34. The optimum condition of production was obtained by adding initiator treatment on the 3rd day for 14 days incubation with the highest yield and could inhibit the growth of all pathogenic microbes.